A valence tautomeric dinuclear copper tetrakisguanidine complex - Wiesner, Sven; Wagner, Arne; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2016)
We report on the first valence tautomeric dinuclear copper complex, featuring 2,3,5,6-tetrakis(tetramethylguanidino)pyridine as a bridging redox-active GFA (guanidino-functionalized aromatic) ligand. The preferred electronic structure of the complex is massively influenced by the environment. In the solid state and in nonpolar solvents a paramagnetic, dinuclear CuII complex with a neutral GFA ligand is present. In polar solvents, the electronic structure changes to a diamagnetic, dinuclear CuI complex with a twofold-oxidized GFA ligand. Using acetone as a solvent, both electronic structures are accessible due to a temperature-dependent equilibrium between the two valence tautomeric complexes. Our results pave the way for a broader use of valence tautomeric transition-metal complexes in catalytic reactions since anionic coligands can now be tolerated owing to the neutral/positively charged GFA ligand.
Gesehen am 24.08.2020